Revision der von Reitter & Croissandeau im Jahr 1890 aus der Umgebung von Blumenau im Staate Santa Catarina in Südbrasilien beschriebenen Scydmaeniden (Coleoptera, Scydmaenidae). - Franz, Herbert (Contributions to Entomology = Beiträge zur Entomologie, 1993)
Reitter and Croissandeau described so shorts 41 species of Scydmaendae, moustly collected by Hetschko in southern Brasil, that they can not be identify. This material is deposited now in the Deutschen Entomologisches Institut in Eberswalde (BRD) and was revised by me. The result of this revision is published in this paper. All together 36 species could be identified, Lectotypes where selected. The following exchanges of names must take place: - Scydmaenus saupauloi Franz (1980) is Synonym of Scydmaenus denticornis Reitter & Croiss. (1890), Euconnus fugitor Reitter and Croissandeau is a synonym of E. latipennis Reitter and Croissandeau. The original diagnoses of Euconnus permixtus and vestitus are mixt from the authors, so that they are not valuable. These species are described by Franz (1980) newly under the names nidicola Franz and globicollis Franz (1980) and these are the first valuable descriptions. From the typeseries of Euconnus ovipennis Reitter and Croissandeau only 1 represents this species. This specimen was selected as Lectotype, the other 4 specimens belong to Euconnus latipennis Reitter & Croiss. also two species are mixt. From the two specimens existing under this name one was selected from me as Lectotypus, the other represents a new species, I named pseudoclanculus. The collection contain also a new species named i.l. by the authors Euconnus micropterus, the description of this species is given.Nomenclatural Actsarion Reitter & Croissandeau, 1890 (Euconnus), Lectotypeclanculus Reitter & Croissandeau, 1890 (Euconnus), Lectotypeeques Reitter & Croissandeau, 1890 (Euconnus), Ledctotypeexcedens Reitter & Croissandeau, 1890 (Euconnus), Lectotypefugitor Reitter & Croissandeau, 1890 (Euconnus), syn. n. of Euconnus latipennis Reitter & Croissandeau, 1890hetschkoi Reitter & Croissandeau, 1890 (Euconnus), Lectotypelepidus Reitter & Croissandeau, 1890 (Euconnus), Lectotypelothari Reitter & Croissandeau, 1890 (Euconnus), Lectotypemicropterus Franz, 1993 (Euconnus), spec. n.pachyscelis Reitter & Croissandeau, 1890 (Euconnus), Lectotypepauper Reitter & Croissandeau, 1890 (Euconnus), Lectotypepseudoclaculus Franz, 1993 (Euconnus), spec. n.subcompressus Reitter & Croissandeau, 1890 (Euconnus), Lectotypepermixtus Reitter & Croissandeau, 1890 (Euconnus (Pycnophus)), Lectotypevestitus Reitter & Croissandeau, 1890 (Euconnus (Pycnophus)), Lectotypeminimus Reitter & Croissandeau, 1890 (Microscydmus (Neoscydmus)), Lectotypepseudodilatatus Franz, 1993 (Scydmaenus), spec. n.saopauloi Franz, 1980 (Scydmaenus), syn. n. of Scydmaenus denticornis Reitter & Croissandeau, 1890